Dampak Krisis Ekonomi terhadap Distribusi Pendapatan di Indonesia: Analisa SNSE Indonesia 1995 dan 1998 - Wibisono, Yusuf (UI Scholars Hub, 2003)
This paper examines the income distributional impact of the 1997s economic crisis that hit Indonesia using Social Accounting Matrix data for 1995 and 1998. Relying on a comparison of the distribution before and after crisis, the study suggests three main findings based on multiplier analysis. First, poor households have been harder hit by crisis than rich households. Second, there are indication that crisis making income transfer likely to occurs from consumer to producer. Third, it is hard to eliminate disparity in income distribution relying only on market mechanism. From impact analysis we obtain the result for policy recommendation. Agriculture price support policy tend to biased to rural rich households, while export promotion policy biased to urban rich households. Direct income transfers to poor household and income redistribution policy seems to be the best policy for improving the distribution of income after crisis.